Histopathological and enzymatic study on the effect of Aspergillus fumigatus in mice - Shafiq, Shatha A; Al- Joofy, Akbal K. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: - Aspergillus fumigatus is a ubiquitous and opportunistic fungal pathogen causing sever invasive aspergillosis, an important source of morbidity and mortality in immunocompromised hosts (human and animals) .The present study was conducted to obtain more clarification about the toxicity and histopathological effects of this pathogen in albino mice Material and Methods :- fourteen male mice( 6-10) weeks old ,( 20 – 28) gm weight , divided into two groups , test group ( n= 8) , intranasally infected with 25μl (710 conidia / ml normal saline ) of A. fumigatus for 7 successive days , compared with uninfected group ( n=6) . the weight of all animals were measured at the beginning and at the end of the experiment , in addition to histological study for lung , liver and kidney were performed , with estimation of enzyme activity of GOT ( Glutomic Oxaloacetic Transaminase),GPT (Glutamic Pyruvic Transaminase) , ALP (Alkaline Phosphatase ) and Creatinine Kinase in homogenized liver and kidney tissues were studied by colorimetric method . Results :- increased ( p< 0.05) in body weight , and organs weight ( lung , liver , kidney ) in infected mice with different histological changes were found in organs tissues of infected mice especially in lung and liver , these changes were supported by variation in enzyme activities of GOT, GPT, ALP and Creatinin kinase in homogenized organs tissues Conclusion: - normal host can suffer from systematic diseases after inhalation of infective forms of A. Fumigatus (conidia), and further work is needed to study the active components, which are responsible for pathogenesis of this opportunistic fungi